(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The development of corpus linguistics has fundamentally transformed contemporary linguistic research by introducing empirical and data driven approaches to language analysis. Among various corpus types, parallel corpora occupy a significant position due to their ability to facilitate cross-linguistic investigations and translation-oriented studies. However, the scientific value of a parallel corpus largely depends on the quality and comprehensiveness of its annotation. Annotation serves as a crucial intermediary layer between raw textual data and linguistic interpretation, enriching corpus materials with morphological, syntactic, semantic, pragmatic, and translational information. This paper examines the theoretical foundations and methodological principles of parallel corpus annotation and discusses its role in translation studies, comparative linguistics, and paremiological research. Particular attention is devoted to sentence alignment, linguistic tagging, and proverb annotation within bilingual corpora. The study argues that corpus annotation significantly enhances the analytical potential of parallel corpora and contributes to the advancement of corpus-based linguistic and translation research.